Досвід ведення пацієнтів із гіперпролактинемією при підготовці до допоміжних репродуктивних технологій - Нікіфоров, Олег Анатолійович; Ломейко, Олена Олександрівна; Авраменко, Наталія Вікторівна; Никифоров, О. А.; Ломейко, Е. А.; Авраменко, Н. В.; Nikiforov, O. A.; Lomeiko, E. A.; Avramenko, N. V. (My University, 2017)
У статті розглядається досвід ведення пацієнтів з гіперпролактинемією при підготовці до допоміжних репродуктивних технологій. Встановлено, що гіперпролактинемія у чоловіків спричиняє вірогідні зміни кількісних та якісних показників спермограми у вигляді зниження концентрації (р<0,05) та кількості сперматозоїдів (р<0,05) в еякуляті, зменшенням кількості рухливих форм (р<0,05), зростанням кількості гіпокінетичних (р<0,05) та акінетичних (р<0,05) форм, морфологічно – редукцією нормальних форм (р<0,05) на користь дегенеративних (р<0,05), а також збільшенням кількості клітин сперматогенезу (р<0,05). Виявлено, що призначення бромокриптину у інфертильних чоловіків з гіперпролактинемією сприяє зниженню рівня пролактину (р<0,05), зростанню вмісту фолікулотропного (р<0,05) та лютеотропного гормонів (р<0,05), збільшенню рівня тестостерону та тестостерон/естрогенового (р<0,05) співвідношення. Доведено, що на фоні застосування бромокриптину у гіперпролактинемічних чоловіків відбувається стимуляція процесів сперматогенезу з вірогідним приростом в показниках спермограми концентрації та кількості сперматозоїдів (р<0,05), кількості клітин з нормальною рухливістю (р<0,05), редукцію гіпокінетичних (р<0,05) та акінетичних (р<0,05) сперматозоїдів, а також зменшенню кількості дегенеративних форм (р<0,05). . В статье рассматривается опыт ведения пациентов с гиперпролактинемией при подготовке к вспомогательным репродуктивным технологиям. Установлено, что гиперпролактинемия у мужчин вызывает достоверные изменения количественных и качественных показателей спермограммы в виде снижения концентрации (р<0,05) и числа сперматозоидов (р<0,05) в эякуляте, уменьшения количества подвижных форм (р<0,05), прироста числа гипокинетических (р<0,05) и акинетических (р<0,05) форм, морфологически – редукцией нормальных клеток (р<0,05) в пользу дегенеративных (р<0,05), а также увеличением количества клеток сперматогенеза (р<0,05). Выявлено, что назначение бромокриптина у инфертильных мужчин с гиперпролактинемией способствует снижению уровня пролактина (р<0,05), приросту фоликулотропного (р<0,05) и лютеотропного гормонов (р<0,05), а также уровня тестостерона и тестостерон/эстрогенового (р<0,05) соотношения. Доказано, что на фоне применения бромокриптина у гиперпролактинэмичных мужчин происходит стимуляция процессов сперматогенеза с достоверным приростом концентрации и числа сперматозоидов (р<0,05) в показателях спермограммы, числа клеток с нормальной подвижностью (р<0,05), редукцией гипокинетических (р<0,05) и акинетических (р<0,05) сперматозоидов, а также уменьшением числа дегенеративных форм (р<0,05). The aim – to research the results of diagnostic and treatment male infertility during hyperprolactinemia and preparing for assisted reproductive technologies are presented at the article. Object and methods. 58 men were included in the research. It was formed two different groups – with normoprolactinemia (27 persons, group 1) and hyperprolactinemia (21 persons, group 2). It has done the typical clinical and biochemical investigation in all patients. For the research of spermogram parameters it was used the method of luminescent microscopy. At the patients with hyperprolactinemia the magnetic resonant tomography or computed tomography for diagnostics of hypophysis adenomas was used. At 19 patients with male infertility and hyperprolactinemia was used semisynthetic alkaloid bromocriptine for systemic treatment (the dosage 2,5 mg twice per day during 4 weeks). Results. It is set that hyperprolactinemia causes the reliable changes of spermogram parameters with the reduction of concentration (р<0,05) and numerous of spermatozoas (р<0,05), decreasing of normokinetic forms (р<0,05), increasing of hypokinetic (р<0,05) and akinetic (р<0,05) forms, morphologically it was set the reduction of normal cells (р<0,05) and presenting of degenerative cells (р<0,05). It is revealed, that usage of bromocriptine for male infertility with hyperprolactinemia promotes the decline of prolactin level (р<0,05), increases the follicle-stimulating hormone (р<0,05) and luteotrophic hormone (р<0,05), and also the level of testosterone and testosterone/oestrogen (р<0,05) ratio. It is proved that bromocriptine application at the men with hyperprolactinemia stimulates the processes of spermatogenesis with the reliable increase of spermatozoas number (р<0,05), especially normokinetic forms (р<0,05), with the reduction of hypokinetic (р<0,05) and akinetic (р<0,05) spermatozoas, and also with the reduction of degenerative forms (р<0,05). Conclusion. The male patients with infertility and hyperprolactinemia have reliable changes of spermogram parameters with the reduction of concentration and numerous of spermatozoas, normokinetic forms, increasing of hypokinetic and akinetic forms, morphologically. Bromocriptine implementation during male infertility with hyperprolactinemia gives a good results for processes of spermatogenesis, so it could be high effective during additional reproductive technologies.
Опыт ведения пациентов с гиперпролактинемией при подготовке к вспомогательным репродуктивным технологиям
Experience with taking care of hyperprolactinemia patients during prevention for assisted reproductive technologies
Keywords: чоловіче безпліддя; гіперпролактинемія; спермограма; бромокриптин; мужское бесплодие; гиперпролактинемия; спермограмма; бромокриптин; male infertility; hyperprolactinemia; spermogram; bromocriptine